Synthesis and characterization of PLGA nanoparticles encapsulating bioactive ingredients from mango fruit waste and investigation on their antioxidant and antibacterial properties - Abd El Aal, Sherine Saad Metwally (AUC Knowledge Fountain, 2018)
[not available]